The Influence of Behavioral Bias on Investment Decision with Risk Perception as a Mediating Variable: A Study on Generation Z at the Indonesia Stock Exchange - Willie Kurnijanto, Aldo; Joni, Joni; Videlia Sumbodo, Karen; Inggrit Wijaya, Liliana; Silvia Sutejo, Bertha (Dinasti Publisher, 2025)
This study uses structural equation modeling to examine the direct and indirect relationships between behavioral biases and investment decisions with the mediating role of risk perception. This study was conducted among Generation Z individual investors who have been investing on the Indonesia Stock Exchange for several months to years. The behavioral biases examined include overconfidence bias, herding bias, and loss aversion bias, with data from 300 respondents collected through purposive sampling. The results show that risk perception mediates the relationship between overconfidence bias, herding bias, and loss aversion bias with investment decisions. Herding bias and loss aversion bias were found to have a direct relationship with risk perception. In addition, it was also found that herding bias, loss aversion bias, and risk perception have a direct relationship with investment decisions. This research is essential for investors to make more rational investment decisions and improve investment performance by recognizing the risks associated with behavioral biases. The increasing number of retail investors and Generation Z on the Indonesia Stock Exchange demands sound investment decisions. Behavioral biases often trigger irrational decisions and errors in portfolio management, while risk perception can strengthen or weaken the impact of behavioral biases on investment decisions. This study contributes theoretically to investment and behavioral finance, particularly regarding the mediating effect of risk perception.